Impact of transjugular intrahepatic portosystemic shunt implantation on liver perfusion measured by volume perfusion CT. (October 2017) - Preibsch, Heike; Spira, Daniel; Thaiss, Wolfgang M; Syha, Roland; Nikolaou, Konstantin; Ketelsen, Dominik; Lauer, Ulrich M; Horger, Marius
Background: Implantation of a transjugular intrahepatic portosystemic shunt (TIPS) induces changes of liver perfusion. Purpose: To determine the changes in arterial, portal venous, and total perfusion of the liver parenchyma induced by TIPS using the technique of volume perfusion computed tomography (VPCT) and compare results with invasively measured hepatic intravascular pressure values. Material and Methods: VPCT quantification of liver perfusion was performed in 23 patients (mean age, 62.5 ± 8.8 years) with portal hypertension in the pre-TIPS and post-TIPS setting, respectively. A commercially available software package was used for post-processing, enabling separate calculation of the dual (arterial [ALP] and portal venous [PVP]) blood supply and additionally of the hepatic perfusion index (HPI) (HPI = ALP/(ALP + PVP)*100%). Invasive pressure measurements were performed during the intervention, before and after TIPS placement. Liver function tests performed before and after the procedure were compared. Results: Mean decrease of pressure gradient through TIPS was 13.3 mmHg. Mean normal values for ALP, PVP, and total perfusion (ALP + PVP) before TIPS were 15.9, 37.7, and 53.5 mL/100 mL/min, respectively, mean HPI was 35.4%. After TIPS, ALP increased to a mean value of 37.7 mL/100 mL/min, PVP decreased (15.7 mL/100 mL/min, P  < 0.05), whereas total perfusion remained unchanged (53.4 mL/100 mL/min, P  = 0.97). HPI increased (71.9%; P  < 0.05). No correlation between invasive pressure measurement and VPCT parameters was observed. After TIPS, liver function tests were found to worsen with a significant increase of bilirubin ( P  < 0.05). Conclusion: Following TIPS placement, ALP and HPI increased in all patients, whereas PVP markedly decreased. Interestingly, the magnitude of decrease in portosystemic pressure gradients was not found to correlate with VPCT parameters.